Identification of liquids in different containers using a microwave planar metamaterial - Nedukh, S.V.; Polevoy, S.Y.; Tarapov, S.I.; Vakula, A.S. (Радіофізика та електроніка, 2017)
At present, the fast contactless identification of liquids enclosed into a container has a practical importance. The identification of liquids can be required, for example, at airports, in order to prevent the transport of illicit liquids in bottles. However, the complexity of applying contactless methods lies in the difficulties to take into account the influence of container characteristics. In this paper, a metamaterial based on two planar photonic crystals (PPC) has been applied for the experimental analysis of liquids in different containers. It was shown experimentally how the transmission coefficient spectrum of PPC varied with changing the characteristics of a container with a liquid. Namely, the influence of thickness and material of the container walls and the inclination angle of its axis relative to the metamaterial plane on the transmission coefficient has been studied. The reliable differing of concentration increments of edible salt and sugar in water was determined as 10 %. It is shown that an increase of the container walls thickness leads to a decrease of the reliability of the liquid identification in it. Thus, the influence of some container characteristics on the reliability of contactless identification of liquids by using PPC has been taken into account. Быстрая бесконтактная идентификации жидкостей, находящихся в сосуде, представляет большой практический интерес. Данный способ идентификации может применяться, например, в аэропортах, с целью предотвращения провоза в багаже запрещенных жидкостей. Однако применение бесконтактных методов осложняется необходимостью учета влияния характеристик сосуда. В настоящей работе метаматериал на основе двух планарных фотонных кристаллов (ПФК) был применен для экспериментального анализа жидкостей, находящихся в различных сосудах. Экспериментально показано, каким образом изменялся спектр коэффициента пропускания ПФК с изменением характеристик сосуда с жидкостью. Исследовано влияние толщины и материала стенок сосуда, угла наклона его оси относительно плоскости метаматериала на его коэффициент прохождения. Приращение концентрации пищевой соли и сахара в воде при надежном различении растворов было определено как 10 %. Показано, что увеличение толщины стенки сосуда приводит к снижению надежности идентификации жидкости в нем. Таким образом, было учтено влияние некоторых характеристик сосуда на надежность бесконтактной идентификации жидкостей с использованием ПФК. Швидка безконтактна ідентифікація рідин, що знаходяться в посудинах, становить великий практичний інтерес. Такий спосіб ідентифікації може застосовуватися, наприклад, в аеропортах, з метою запобігання провезення у багажі заборонених рідин. Однак застосування безконтактних методів ускладнюється необхідністю урахування впливу характеристик посудини. У цій роботі метаматеріал на основі двох планарних фотонних кристалів (ПФК) був застосований для експериментального аналізу рідин, що знаходяться в різних посудинах. Експериментально показано, яким чином змінювався спектр коефіцієнту пропускання ПФК зі зміною характеристик посудини з рідиною. Досліджено вплив товщини і матеріалу стінок посудини, кута нахилу її осі відносно площини метаматеріалу на його коефіцієнт проходження. Приріст концентрації харчової солі і цукру у воді за умов надійного розрізнення розчинів було визначено як 10 %. Показано, що збільшення товщини стінки посудини призводить до зниження надійності ідентифікації рідини в ній. Таким чином, було враховано вплив деяких характеристик посудини на надійність безконтактної ідентифікації рідин з використанням ПФК.